(untitled) - Miller, William J. (New York, 1939)
In the preparation of this book the author has attempted to present, in popular form, the salient points of a general survey of the whole great scinece of geology, the science which deals with the history of the earth and its inhabitants as revealed in the rocks.
Keywords: Địa chất học,Geology